Direito fundamental de proteção do consumidor e a desterritorialização do mercado - Fonseca Neto, Javert Ribeiro da (Universidade do Vale do Rio dos Sinos, 2012)
Brazilian consumer rights in the globalized age, the topic being discussed in this research focuses on discussing the defense of consumer laws then existing, confronting them with the changes arising from the consumer society arising from the phenomenon of globalization, especially in this time that this networked society, where the 'internationalization of market and of law' introduced a new type of vulnerability (especially) the consumer. Check if the current legal system meets the desire for social security in respect of consumption. The subject matter should be addressed within the specific boundaries of space and time appointed for this debate. In other words: Reflections supported by contemporary society (time) consumption in the context of our nation-state (space), arising from the phenomenon of unbridled globalization and regulatory system of protection of consumer protection in force in our times and their social worth.
Keywords: Right; Vulnerability; Society; Globalization; Constitutional protection of the consumer; Direito; Vulnerabilidade; Sociedade; Globalização; Proteção constitucional do consumidor; ACCNPQ::Ciências Sociais Aplicadas::Direito